Information Literacy Related to Physical Fitness: Identification of University Students’ Ability to Access, Process, and Utilize Information in Supporting a Healthy Lifestyle - Susanto, Indra Himawan; Suherman, Wawan; Mustar, Yetty Septiani; Irawaty, Irawaty (STKIP PGRI Trenggalek, 2026)
The use of physical fitness information is important in supporting students to make decisions related to healthy lifestyles and prevention of health risks. This research aims to identify the literacy of students' physical fitness information based on the ability to access, process, and utilize information. The research uses a quantitative approach with a survey design on college students. The instruments are compiled based on the Empowering Eight indicators which are grouped into three domains, namely access, processing, and utilization of information. Data were analyzed using descriptive statistics and the Mann–Whitney test to test for differences by gender. The results of the study show that the literacy of students' physical fitness information is in the medium category. Significant differences were found in the indicators of exploration, selection, organization, presentation, and application of information. Male students tend to get higher scores in the aspects of exploration, organization, communication, and application of information, while female students are more selective in choosing information. These findings show the need to strengthen physical fitness information literacy through fitness education and digital health information evaluation training to support students' healthy living behaviors.